2011
DOI: 10.1111/j.1475-1305.2009.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Accurately Measuring Mechanical Properties on the Micro‐Scale

Abstract: A methodology has been developed for accurately measuring the mechanical properties of materials used on the micro-scale. The direct tension test method using a dog bone-type specimen has been employed, as it is the most effective and straightforward method to obtain results including a full stress-strain curve. The goal of this investigation was to develop a universal, yet simple and reliable, methodology to be used for accurate characterisation of mechanical properties for a wide variety of materials. Specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…However, there is a growing community of researchers working on innovative experiments to investigate and validate microscale models. Some of the promising approaches that need to be investigated further include: Banks-Sill et al [198] in situ microscale tensile tests, Szczepanski and co-workers microscale fatigue experiments [199]; Chan et al [203] microscale plastic deformation experiment in microforming processes [200]; Kimberly and co-workers' [204] dynamic response of micro-machined beams; Katsamenis et al [201] lamellar level cortical bone load bearing characterization. All these approaches describe an objective process of understanding the microscale behaviour of heterogeneous materials.…”
Section: The Quest For High-fidelity Experimental Datamentioning
confidence: 99%
“…However, there is a growing community of researchers working on innovative experiments to investigate and validate microscale models. Some of the promising approaches that need to be investigated further include: Banks-Sill et al [198] in situ microscale tensile tests, Szczepanski and co-workers microscale fatigue experiments [199]; Chan et al [203] microscale plastic deformation experiment in microforming processes [200]; Kimberly and co-workers' [204] dynamic response of micro-machined beams; Katsamenis et al [201] lamellar level cortical bone load bearing characterization. All these approaches describe an objective process of understanding the microscale behaviour of heterogeneous materials.…”
Section: The Quest For High-fidelity Experimental Datamentioning
confidence: 99%
“…While the literature on the application of DIC for strain and micron-scale displacement measurements are voluminous, its use at the nanoscale is less explored. The implementation of DIC algorithms for the extraction of nanoscale displacements and the acquisition of surface data by means of AFM (Zhu et al 2003) or optical microscopy (Banks-Sills et al 2010) was reported mainly in connection with strain calculations and in the framework of tensile test experiments.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution DIC processing of optically imaged displacements was reported in the literature as well [47] including optically imaged MEMS devices [37,[48][49][50][51][52][53][54]. Although optical microscopy achieves lower magnifications, there are many benefits, such as insensitivity to electrostatic fields [48,49,51] and a high sampling rate [52,54].…”
Section: Introductionmentioning
confidence: 99%
“…The matching procedure is completed through optimization of the correlation criterion using the Newton-Raphson method to find the peak position of the distribution of the correlation criterion and to determine the displacement in the deformed image [30,34]. DIC algorithms were expanded to calculate strain by differentiating the displace- ment field, or more commonly by differentiating the smoothed displacement field [32,[37][38][39]. In recent years DIC algorithms were further improved to detect three-dimensional displacements.…”
Section: Introductionmentioning
confidence: 99%